Internet of Things (IoT) Scheme in Blank Spot Area for PV Smart Grid System - Hadi Pramono, Sholeh; Nur Hasanah, Rini; Maulana, Eka; Hario Patriansyah, Fakhriy; Zainuri, Akhmad (International Journal of Engineering and Technology, 2018)
Application of the IoT (Internet of Things) for energy management systems has been implemented in a wide area. The wireless monitoring on the PV smart grid system commonly is encountered in the urban area which GSM covered area. In this paper, a blank spot area without the GSM signal for data transmitting via internet information is selected to characterized for optimizing the energy monitoring system due to the deployment of this system is in an out of reach area. In practice, this condition occurs in a forest, beach or outermost coverage areas. This monitoring technique of electric power based on the client-server internet of things is designed with the experimental verification using a combination of RF Lora communication for a blank spot area and Wi-Fi module for the coverage sector. In this study, the method used in the monitoring mechanism was using wireless communication via internet Wi-Fi module which can be accessed through a website. This system was conducted in monitoring the current and voltage on the load by using current and voltage sensors, then the data is converted into the power. This system is also capable of performing monitoring via an online system based on the web server and ubiquitous access. This scheme has the capability of reading up to 40A current changes and the change in voltage up to 24V. The data processing on the microcontroller will be stored on the memory card for being data loggers and sent to the web server for the real-time monitoring system wirelessly. This system can be used for the control mechanisms of future smart grid networks based on the IoT (Internet of Things) for the blank spot area without GSM or Wi-Fi connection directly.Â Â Â